Phytochemical Screening and Cytotoxic Analysis of - BABA-MOUSSA, FARID A. KADER SAÏD; BANKOLE, HONORÉ SOUROU; DOUGNON, T. VICTORIEN; AGBANKPE, J. (My University, 2015)
The use of plants in traditional medicine become very common nowadays throughout the world and in developing countries in particular. The current study was carried out aiming to compare the chemical features of three vegetables (Vernonia amygdalina, Crateva adansonii and Sesamum radiatum) mostly used for human consumption and traditional medicine to treat bacterial diarrhoea in Benin. These vegetables were selected among the 27 species obtained after ethno-botanical investigations in southern Benin. Therefore, the major chemical groups contained in these vegetables were detected by solubility assays together with coloration and precipitation reactions. Furthermore, cytotoxicity of the plant extracts was assessed on shrimp larvae (Artemia salina). The results showed that gallic tannins, flavonoids, alkaloids, mucilages, coumarins and reducing compounds were detected in all samples (100%) followed by cathechic tannins (66.66%) and saponins (33.33%). The study also revealed that none of the studied vegetables is cytotoxic (LC50 > 0.01 mg/ml). This study was conducted in the perspective of establishing innovations capable of assisting to; manufacture Improved Traditional Medicines for the treatment of bacterial diarrhoea in the future. Besides, it pointed out the presence of secondary metabolites and the cytotoxicity of these vegetables interesting for further antibacterial, antidiarrheal and pharmacological studies.
Keywords: Vernonia amygdalina; Crateva adansonii; Sesamum radiatum; phytochemical screening; cytotoxicity.